Bioactive Molecules for Skin Repair and Regeneration: Progress and Perspectives - Deyun Chen; Qian Hou; Lingzhi Zhong; Yali Zhao; Meirong Li; Xiaobing Fu (Stem Cells International)
Skin regeneration is a vexing problem in the field of regenerative medicine. A bioactive molecule-based strategy has been frequently used in skin wound healing in recent years. Bioactive molecules are practical tools for regulating cellular processes and have been applied to control cellular differentiation, dedifferentiation, and reprogramming. In this review, we focus on recent progress in the use of bioactive molecules in skin regenerative medicine, by which desired cell types can be generated in vitro for cell therapy and conventional therapeutics can be developed to repair and regenerate skin in vivo through activation of the endogenous repairing potential. We further prospect that the bioactive molecule-base method might be one of the promising strategies to achieve in situ skin regeneration in the future.